Adjuvant Chemotherapy for Pathological Node-Positive Disease in Squamous Cell Carcinoma of the Esophagus after Neoadjuvant Chemoradiotherapy Plus Surgery - Lin, Jing-Wei; Li, Chuan; Yeh, Hui-Ling; Chuang, Cheng-Yen; Chen, Chien-Chih (Journal of personalized medicine, 2022)
Purpose: The purpose of the present study is to determine the impact on survival using adjuvant chemotherapy on patients with locally advanced esophageal cancer. Materials and Methods: From 2007 to 2016, we enrolled 127 locally advanced esophageal squamous cell carcinoma patients treated with combined neoadjuvant chemoradiotherapy (nCRT) and surgery. For patients with the pathological residual primary disease (pT+) and/or residual node disease (pN+) after nCRT, adjuvant chemotherapy was also given after consideration of the toxicity of nCRT, patient performance, and/or comorbidity. The regimen of adjuvant chemotherapy was cisplatin 20 mg/m2/day and 5-fluorouracil 800 mg/m2/day on days 1 through 4 and 22 through 25. The primary endpoint was overall survival (OS). Results: From a total of 127 patients, 26 of them (20.5%) received adjuvant chemotherapy. In the multivariate analysis, pN+ diseases were independently associated with poor OS (hazard ratio (HR): 4.117, 95% confidence interval (CI): 1.366–12.404; p = 0.012). For those with pN+ diseases, their 5-year OS was 36.4% in the follow-up arm compared with 45.8% in the adjuvant chemotherapy arm (p = 0.094). Conclusions: Pathologic node-positive disease is associated with poor OS in locally advanced esophagus cancer patients after combined treatments with nCRT and surgery. Adjuvant chemotherapy appeared to have improved OS in pathologic node-positive diseases.